School choice and information : An experimental study on matching mechanisms - Pais, Joana (2022)
We present an experimental study where we analyze three well-known matching mechanisms—the Boston, the Gale–Shapley, and the Top Trading Cycles mechanisms—in different informational settings. Our experimental results are consistent with the theory, suggesting that the TTC mechanism outperforms both the Boston and the Gale–Shapley mechanisms in terms of efficiency and it is slightly more successful than the Gale–Shapley mechanism regarding the proportion of truthful preference revelation, whereas ma nipulation is stronger under the Boston mechanism. In addition, even though agents are much more likely to revert to truth-telling in lack of information about the others’ payoffs—ignorance may be beneficial in this context—the TTC mechanism results less sensitive to the amount of information that participants hold. These results therefore suggest that the use of the TTC mechanism in practice is more desirable than of the others..